Brain-Derived Steroids, Behavior and Endocrine Conflicts Across Life History Stages in Birds: A Perspective - Wingfield, John C.; Wacker, Douglas W.; Bentley, George E.; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2018)
Biological steroids were traditionally thought to be synthesized exclusively by the adrenal glands and gonads. Recent decades have seen the discovery of neurosteroid production that acts locally within the central nervous system to affect physiology and behavior. These actions include, for example, regulation of aggressive behavior, such as territoriality, and locomotor movement associated with migration. Important questions then arose as to how and why neurosteroid production evolved and why similar steroids of peripheral origin do not always fulfill these central roles? Investigations of free-living vertebrates suggest that synthesis and action of bioactive steroids within the brain may have evolved to regulate expression of specific behavior in different life history stages. Synthesis and secretion of these hormones from peripheral glands is broadcast throughout the organism via the blood stream. While widespread, general actions of steroids released into the blood might be relevant for regulation of morphological, physiological, and behavioral traits in one life history stage, such hormonal release may not be appropriate in other stages. Specific and localized production of bioactive steroids in the brain, but not released into the periphery, could be a way to avoid such conflicts. Two examples are highlighted. First, we compare the control of territorial aggression of songbirds in the breeding season under the influence of gonadal steroids with autumnal (non-breeding) territoriality regulated by sex steroid production in the brain either from circulating precursors such as dehydroepiandrosterone or local central production of sex steroids de novo from cholesterol. Second, we outline the production of 7α-hydroxypregnenolone within the brain that appears to affect locomotor behavior in several contexts. Local production of these steroids in the brain may provide specific regulation of behavioral traits throughout the year and independently of life history stage.